2015
DOI: 10.4238/2015.february.13.23
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of pathologic nipple discharge

Abstract: ABSTRACT. The cause of pathologic nipple discharge is mainly benign lesions, but there is still a possibility of malignancy. Pathologic nipple discharge may be the only or the first symptom of breast cancer. This study aimed to investigate the clinical factors associated with lesions in patients with pathologic nipple discharge using a retrospective analysis of clinical data in 207 cases. The univariate analysis showed that age >50 years, breast lumps, or breast calcifications were risk factors associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The cause of pathologic nipple discharge is primarily benign lesions, but there is still a possibility of malignancy [16]. Pathologic nipple discharge patients with breast microcalcifications had a higher risk of breast cancer than those without breast calcifications ( p = 0.000) [17].…”
Section: Discussionmentioning
confidence: 99%
“…The cause of pathologic nipple discharge is primarily benign lesions, but there is still a possibility of malignancy [16]. Pathologic nipple discharge patients with breast microcalcifications had a higher risk of breast cancer than those without breast calcifications ( p = 0.000) [17].…”
Section: Discussionmentioning
confidence: 99%
“…Benign nipple discharge is most often bilateral, nonbloody, and nonspontaneous. 4 On the contrary, pathologic nipple discharge, as seen in this patient, is most often unilateral, bloody, and spontaneous. 4 Recent studies indicate that up to 25% of patients with pathologic nipple discharge will have underlying breast cancer.…”
Section: Discussionmentioning
confidence: 66%
“… 4 On the contrary, pathologic nipple discharge, as seen in this patient, is most often unilateral, bloody, and spontaneous. 4 Recent studies indicate that up to 25% of patients with pathologic nipple discharge will have underlying breast cancer. For patients with breast cancer presenting with only pathologic nipple discharge, mammography is of limited sensitivity (10% to 57%).…”
Section: Discussionmentioning
confidence: 66%
“…Currently, there are no proven predictive models for malignancy in these patients. Surgical selective duct excision still remains the gold standard for treatment (3,5,12,13). In our study, 18% of all cases (60/344) were confirmed to have malignancy.…”
Section: Discussionmentioning
confidence: 99%